Screenhouse and field persistence of nonpathogenic endophytic Fusarium oxysporum in Musa tissue culture plants - Paparu, P.; Dubois, T.; Gold, Cliford S.; Niere, B.; Adipala, E.; Coyne, Danny L. (Springer, 2008)
Two major biotic constraints to highland cooking banana (Musa spp., genome group AAA-EA) production in Uganda are the banana weevil Cosmopolites sordidus and the burrowing nematode Radopholus similis. Endophytic Fusarium oxysporum strains inoculated into tissue culture banana plantlets have shown control of the banana weevil and the nematode. We conducted screenhouse and field experiments to investigate persistence in the roots and rhizome of two endophytic Fusarium oxysporum strains, V2w2 and III4w1, inoculated into tissue-culture banana plantlets of highland cooking banana cultivars Kibuzi and Nabusa. Re-isolation of F. oxysporum showed that endophyte colonization decreased faster from the rhizomes than from the roots of inoculated plants, both in the screenhouse and in the field. Whereas rhizome colonization by F. oxysporum decreased in the screenhouse (4–16 weeks after inoculation), root colonization did not. However, in the field (17–33 weeks after inoculation), a decrease was observed in both rhizome and root colonization. The results show a better persistence in the roots than rhizomes of endophytic F. oxysporum strains V2w2 and III4w1.